Source Term Calculation of Small Pb-Bi Cooled Non-Refueling Nuclear Power Reactor 20 MWe (SPINNOR 20MWe) - Imron Imron; Zaki Su’ud; Ari Darmawan Pasek (Indonesian Journal of Physics, 2010)
Source term calculation of small Pb-Bi cooled, 15 years non-refueling nuclear reactor 20 MWe (SPINNOR 20MWe) has been performed. The study is limited on activity, toxicity, thyroid and whole body dose. The reactor has an average power density of 187 watt/cm3 with near zero postulated accident propability. The LOCA probability less than that of PWR type because of low pressure condition in the Reactor vessel. The coolant freezing in room temperature can protect nuclide from escaping. Antisipated accident by design capable to protect reactor from unprotected transient over power and unprotected loss of flow accident without scram. In hipotetik scenario accident, there is a sabotage in vessel and core melt when cooling system is lost. Core inventory factor on final cycle is 3,69E+9 Ci/MWth. Except elemental iodine and noble gas, all radionuclides were traped in containment. The source term in containmen 1,8 h after accident for Noble Gas group is 2,38E+09 Ci, Halogen group is 5,12E+08 Ci, Alkali metal group is 3,04E+08 Ci, Tellerium group is 3,99E+07 Ci, BaSr group is 6,80E+07 Ci, Noble Metal group is 2,91E+06 Ci, Lanthanide group is 1,72E+06 Ci, Cerium group is 8,12E+07 Ci. Np-237 is the longest for clearance time about 16.500 years, the most toxic is Xe-138 with α/D reach 7,38E+19. The Source term is used for estimate thyroid dose, in EPZ is 0.89 rem and in LPZ is 0.055 rem below limit constrain PWR 180 rem and 130 rem. The whole body dose in EPZ and LPZ is 0,00132 rem dan 0.000269 rem with PWR Standard 9,74 rem dan 8,54 rem. Based on acceptece criteria of PWR type, the safety requirement of SPINNOR 20MWe is achieved.